The Potential Contribution Of Islamic Religious Education In Strengthening AKM And Character Survey - Kurnia Nur Aliffia; Ulfatussyarifah Ulfatussyarifah; Shodiq Abdullah (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
National Assessment is presented as an improvement effort, one of which is through the Minimum Competency Assessment (AKM) and Character Survey. However, the contribution of Islamic Religious Education (PAI) in supporting this assessment has not been studied in depth. This study aims to analyze the role of PAI in strengthening AKM and Character Survey, as well as identifying its implementation challenges. This study employs a literature review method. The findings indicate that PAI not only plays a role in character development but can also enhance literacy and numeracy through contextual materials such as zakat, inheritance, and analysis of the Quran and Hadith texts. The values in PAI also align with the indicators of the Pancasila Student Profile. However, there are still challenges regarding teacher readiness, infrastructure, and the suboptimal integration of assessment results into learning. This study contributes a new perspective that PAI can be an important part of the national assessment strengthening strategy.